MMT and policy assignment in an open economy context: Simplicity is useful, oversimpliflflication not so much - Arslan Razmi (University of Massachusetts, Department of Economics, 2022)
Modern Monetary Theory (MMT) has recently received significant at- tention in academic and policy circles. Critics question the sustainability of MMT-prescribed approaches to fiscal and monetary policy, especially over extended periods of time, in the presence of international financial markets, and for developing country governments that borrow in foreign currency. I formalize some of these arguments using a dynamic, open economy, Tobin-Markowitz portfolio balance environment that takes into account: (1) the role of expectations in the foreign exchange market and the feedback mechanisms between these and the exchange rate and inflation, and (2) interactions between the current account, debt accumulation, and the goods market. I show that continuous monetary accommodation of fiscal policy by a consolidated authority that targets low interest rates is likely to generate instability and make it hard to maintain full employ- ment with stable inflation. Importantly, this is true even in the absence of rational forward-looking expectations or sovereign foreign indebtedness.
Keywords: E12; E31; E42; E52; E61; F32; 330; Modern Monetary Theory; expectations; endogenous money; balance of payments; fiscal and monetary policy